2009
DOI: 10.4071/1551-4897-6.4.198
|View full text |Cite
|
Sign up to set email alerts
|

The Way to High Volume Fabrication of Lab-on-a-Chip Devices—A Technological Approach for Polymer Based Microfluidic Systems with Integrated Active Valves and Pumps

Abstract: We present a technology platform suitable for the mass production of laboratory-on-a-chip devices made of polymers with integrated active and passive components. The presented microfluidic platform with integrated valves and pumps for active flow management is realized with three layers consisting of two polymer parts separated by a thin elastic TPE (thermoplastic elastomer) membrane welded together in one step. The elastic TPE membrane acts as an integrated deflectable membrane layer between the two outer pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…24 This benchmark was exceeded by far and verifies sufficient bond strength of laser welded COP-TPS-COP multilayer stacks. Since the barrier properties of PC are not sufficient 11 for long-term storage, the reagent reservoirs were coated with layers of Al 2 O 3 in a PEALD (Plasma-Enhanced Atomic Layer Deposition) process.…”
Section: High Temperature Storage and Surface Coatingmentioning
confidence: 88%
See 3 more Smart Citations
“…24 This benchmark was exceeded by far and verifies sufficient bond strength of laser welded COP-TPS-COP multilayer stacks. Since the barrier properties of PC are not sufficient 11 for long-term storage, the reagent reservoirs were coated with layers of Al 2 O 3 in a PEALD (Plasma-Enhanced Atomic Layer Deposition) process.…”
Section: High Temperature Storage and Surface Coatingmentioning
confidence: 88%
“…Rupp et al reported a tensile strength of σ ≈ 2.0 N mm −2 for PC-TPU-PC composites. 24 This benchmark was exceeded by far and verifies sufficient bond strength of laser welded COP-TPS-COP multilayer stacks.…”
Section: Tensile Strengthmentioning
confidence: 88%
See 2 more Smart Citations
“…The upper and lower bulk layers can be structured using high throughput fabrication processes such as injection molding. 20 All three layers are joined together in one laser welding step (Fig. 3) creating a mechanically stable assembly which shows no leakage even at a hydraulic pressure of 0.90 MPa, significantly higher than the control and hydraulic pressures used for operation (10-50 kPa).…”
Section: Micropump Concept and Assemblymentioning
confidence: 99%